Program planning finding the balance - Cottrell, David; Shairo, Leah; Sielberger, Julia; Magna Systems, Inc. (Illinois : Magna Systems Inc., 2005)
The NSACA Accreditatioj standards set the framework for appropriate activities for each developmental level. These standards include: human relationship, indoor and ourdoor environment, activities, safety halth and nutrition and administration. In this video, center directors and group workers demonstrate how they plan and developed schedules, activities, and their trips for children in the context of these standards
Title from title screen
Module 2
School age care
Educational consultant, Leah Shapiro, Julia Sielberger ; camera/editor, Nick Kolias
Narrator: Sheron Shapiro
Keywords: Lesson planning; Curriculum development; School-age child care; Professional development